Associations between blood systemic inflammatory markers and anxiety in Helicobacter pylori-infected patients - Gong, Jiantao; Chen, Fengjuan; Jiang, Bin; Zhou, Bin; Ma, Xiang; Wang, Meilei; Dai, Qingyong; Wang, Shiming; Yang, Xiaojun; Zhao, En (Frontiers in Psychiatry, 2025)
BackgroundChronic Helicobacter pylori (H. pylori) infection is associated with both gastrointestinal symptoms and systemic inflammation, which may contribute to the development of psychiatric disorders, particularly anxiety. Appropriate psychiatric interventions have been shown to significantly enhance treatment outcomes in patients undergoing clinical management for H. pylori infection. Early screening for anxiety in this population is therefore of critical clinical importance. This study aimed to identify potential biomarkers for anxiety detection and evaluate the relationship between these biomarkers and anxiety symptoms in H. pylori-positive individuals.MethodA total of 160 participants (81 H. pylori-positive and 79 H. pylori-negative patients) were enrolled in this study. All participants underwent standardized neuropsychological assessments and venous blood collection. Systemic inflammation indices were derived from routine hematological parameters.Results(1) H. pylori-positive patients showed significantly higher anxiety scores [Hamilton Anxiety Scale (HAMA) and Self-Rating Anxiety Scale (SAS)] and elevated inflammatory markers [systemic immune-inflammation index (SII), systemic inflammation response index (SIRI), and aggregate index of systemic inflammation (AISI)] as compared to H. pylori-negative ones. (2) AISI showed optimal diagnostic accuracy for infection status [area under the curve (AUC) =0.746)], followed by SIRI and SII (both AUC > 0.7). (3) In H. pylori-positive patients, inflammatory markers correlated with both anxiety scores and glial fibrillary acidic protein (GFAP) levels. (4) Interactions between serum GFAP and blood SII and AISI were significantly associated with HAMA and SAS scores in H. pylori-positive patients. (5) The GFAP as the mediator, affected the relationship between the blood levels of systemic inflammatory markers and HAMA and SAS scores in H. pylori-positive patients.ConclusionOur findings suggest systemic inflammation indices contribute to anxiety development in H. pylori infection and may serve as practical biomarkers for anxiety screening.